Hands-On Big Data Modeling : Effective database design techniques for data architects and business intelligence professionals /: Effective database design techniques for data architects and business intelligence professionals. (2018) - Lee, James; Wei, Tao; Mukhiya, Suresh Kumar
No abstract available